III-V OMVPE growth and characterisation of graded AlₓGaₓ₋₁As-GaAs layers and heterointerfaces for the development of GRIN-SCH lasers and Gunn diodes - Thavar, Rajan (Department of Chemical Engineering, 2016)
Bibliography: pages 125-131.